Grain dust explosions steady in 1995 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
There were 14 grain dust explosions reported for the U.S. in 1995 according to Robert W. Schoeff, Professor Emeritus and Consultant, Kansas State University and Ralph Regan, Safety Director, USDA-FGIS. This compares to 15 in 1994 and a ten-year average of 14 explosions.
Keywords: Grain dust; Dust explosions